Does microbial resistance profile change in community-based intra-abdominal infections? Evaluation of the culture results of patients with appendicitis - Tartar, Tugay; Sagmak-Tartar, Ayse; Sarac, Mehmet; Bakal, Unal; Akbulut, Ayhan; Kazez, Ahmet (Turkish J Pediatrics, 2018)
Most common origin of intra-abdominal infections in children is appendicitis. Microorganisms responsible for community-based and hospital-acquired intra-abdominal infections vary. The aim of this study was to evaluate microbial culture outcomes and antibiotic susceptibilities of these microorganisms in samples obtained intraoperatively from pediatric patients with appendicitis, and to define the infectious microorganisms responsible for the community-based intra-abdominal infections in our region, and their antibiotic susceptibilities. This study included 231 patients between 0 and 16 years of age, operated on due to appendicitis between 2014 and 2017. Appendicular tissues were sampled intraoperatively. Antibiogram was studied in case of reproduction in tissue culture. Forms included information on the age and gender of the patients, intra-abdominal event, bacterial growth in microbial culture and antibiogram, antibiotic switch during follow-up, duration of the treatment, complications and outcomes were recorded. No microbial growth was observed following inoculation of the samples obtained from appendiceal tissue of 24.7% patients, whereas growth was positive in 75.3%. Gram negative bacteria were isolated in 94.3% of the patients, whereas gram positive bacteria was isolated in 5.7%. Polymicrobial growth was observed in 2.2% of the patients. E. coli in 79.9%, P. aeruginosa in 5.2%, Enterobacter cloacae in 3.4%, Coagulase-negative staphylococci in 3.4%, Klebsiella spp. in 1.7%, Citrobacter spp. in 1.7%, Enterococcus spp. in 1.7%, Comamonas testosteroni in 1.2% of patients produced. ESBL positivity is present in 51 (36.7%) of 139 E. coli strains reproducing in appendiceal tissue culture. ESBL was positivity detected in one of the reproduced 3 Klebsiella spp. strains. In E. coli, ciprofloxacin resistance as 20.86%, ampicillin-sulbactam resistance as 83.45%, and co-trimoxazole resistance as 41% were found. Our study clearly demonstrates that the resistance profile varies in community-based intra-abdominal infections. Empirical treatment protocols should be revised in especially the patients admitted with septic presentation and where the source control is not possible.
Keywords: intra-abdominal infections; antibiotic susceptibilities; appendicitis; children